Analysis of Bacterial Community level Physiological Profiling on the Fermentation of Traditional Pliek u using BIOLOG EcoPlates - Suji Edwar; Pingkan Aditiawati (School of Life Sciences and Technology, Institut Teknologi Bandung, 2021)
Pliek u is an Acehnese traditional condiment made from fermented coconut (Cocos nucifera) endosperm. The traditional pliek u fermentation process typically involves a diverse bacterial community. This research aimed to discover the physiological profile of the bacterial community diversity in pliek u fermentation. BIOLOGTM EcoPlates was used to obtain the physiological functions of the bacterial community during the pliek u fermentation process. The bacteria were then isolated from EcoPlate substrate to determine the predominant microorganism. Results from the analysis showed that the value of the Average Well Colour Development (AWCD) increased during the EcoPlates incubation period. The AWCD values in sample IV were higher than the AWCD values in samples I, II, and III. PCA analysis showed that the use of EcoPlate substrate by the bacterial community at the beginning of the fermentation was correlated with the substrate groups of carbohydrate and polymer, and with the substrate groups of carbohydrate and the amino acid at the end of the fermentation. The phylogenetic analysis showed that EC1 had a close relation with Pseudomonas azotoformans strain NBRC, while EC3 had a close relation with Psedomonas lundensis strain ATCC 49968. In conclusion, there were changes in the use of EcoPlate substrate and the activities of the bacterial community during the pliek u fermentation process.